Gender Perspective to Vedic Education: Current Practices in Nepal - Timilsina, Rajendra Raj (Dhaulagiri Journal of Sociology and Anthropology, 2016)
Vedic civilization has seen changes in its history- from Satya Yug to current Kali Yug. There were equal rights and duties of both men and women at the beginning. Interpretations of Veda, brought out of the Puranas and externalities made the status unequal. Sanatan Dharma, which is still mainstream of Hinduism, has been challenged by reformist Arya Samaj. As a result, there are interpretive differences as well as practices. Such differences can be seen in contemporary Nepal for the last 130 years. Continuing the differences, classicism has been reviving in the education. This revival also commenced with the same dualism. In this qualitative approach of exploration, two different gurukuls of girls have been observed and analyzed from the field for the purpose of exploring the recent practices. The observation was based on respective scriptures as well as experts' interviews. These data have analyzed the confronting practices on gender in Veda and rooted ideas in contemporary Nepal.